First Test of a Potential Biological Control Agent of Argentine ants (Linepithema humile) - Patricia J. Folgarait; Daniela Goffré (Insects, 2025)
The Argentine ant (Linepithema humile), listed among the world’s 100 worst invasive alien species, is notoriously difficult to control due mainly to its formation of large, expansive supercolonies. Despite the drawbacks of chemical control, biological alternatives have not been previously explored for this species. In this study, we evaluated six native entomopathogenic fungal strains against Argentine ants from four behaviorally distinct supercolonies, identified through aggression assays and collected from both urban and natural sites within the species’ native range. Ants were inoculated with 1 × 108 conidia/mL using three methods: topical application, spray, and immersion. Mortality was recorded over 14 days, and the cause of death was confirmed by fungal outgrowth from cadavers. Among all strains, Beauveria bassiana Li053 consistently induced high mortality across all supercolonies and inoculation methods, with LT50 values between 2 and 5 days and final mortality rates exceeding 80%. Fungal infection was confirmed in 87–92% of cadavers. Dose–response assays revealed that higher conidial concentrations accelerated and increased mortality, with an LC50 estimated at 1 × 106 conidia/mL. These results demonstrate that B. bassiana Li053 is a promising candidate for the biological control of L. humile and merits further evaluation under field conditions.